How Does Bullying Happen in Elementary School? - Bambang Saptono (Jurnal Prima Edukasia, 2022)
Bullying is an activity that is quite disturbing and has the potential to interfere with the achievement of educational goals in elementary schools. The purpose of this study is to identify how bullying occurs at the elementary school level. This research is a qualitative study with a focus on the implementation of education in elementary schools. This study uses a phenomenological design to reveal the facts behind the phenomenon of bullying that occurs in children in elementary school. This research was conducted in an elementary school. Research informants are students, teachers and parents. Interviews are the main data collection technique that has been carried out in this study. The data of this study were analyzed using qualitative analysis. The findings of this study indicate the five main causes of bullying in elementary schools based on the results of this study. The first thing is bullying is done by children who feel more powerful in school. Second, bullying occurs because the victim is very weak, so there is a high potential for bullying from other children. Third, bullying occurs because of feelings of inferiority in children who are victims of bullying. Fourth, bullying occurs because of physical differences. Lastly, bullying occurs because the victim has a disadvantaged economic condition.